(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to identify the attitudes of learners towards the Reform and Rehabilitation Diploma program at the Training and Development Center for Reform and Rehabilitation Centers in Jordan. The study used the analytical descriptive approach, and in this study, the study individuals were selected using the intentional sampling method, the number of (50) students and students.